Wildfowl counts 1956-57 - Atkinson-Willes, G L (Wildfowl, 1957)
One of the main difficulties in assessing trends in the populations of any species by means of wildfowl counts is that continuous records over periods of sufficient length are available from only a small proportion of the waters now counted. In the case of the Tufted Duck (Aythya fuligula), however, it can be shown that the small samples of records available for long periods give much the same picture, in the years to which they are common, as the much larger samples available in more recent years. Five samples of comparative counts have been assembled, varying in size and length from one of 165 waters for the six years, 1950-51 to 1955-56, to one of 601 waters for the single season 1955-56. The patterns of the seasonal fluctuations in the numbers of Tufted Ducks (Aythya fuligula) presented by the five samples are first compared and shown to be similar in the years for which they are all available. From this it is inferred that the smaller samples are as reliable as the larger ones. The trends in population are also examined by this method with the larger samples being used to confirm the results of the longer but smaller ones. During the period 1950-51 to 1955-56 wide variations in the numbers present in October, November, February and March may be detected, with increases in the level of population in these months in 1955-56 and to a lesser extent in 1954-55. In January, however, which is the month in which the population of Tufted is most likely to be stable, no variation between the levels in the six years is detectable. From this it is inferred that although early and late in the season the British wintering population of Tufted may be augmented by varying numbers of immigrants, the basic population in January, after the arrival of the autumn immigrants and prior to the hard-weather influxes, has been constant throughout the six years under review. Examination of relative numbers of Tufted Duck counted in different areas and on different habitats reveals a variety of population patterns. In particular, reservoirs appear to be of great importance, as although they comprise only 20% of the waters counted, they carry up to 60% of the birds recorded throughout most of the winter. As a great deal of information on the size and depth of reservoirs is already available, it is intended that the behaviour of the populations of Tufted on them shall be the subject of a further, more detailed, paper.